Alveolar ridge dimensional changes following ridge preservation procedure: part‐2 – CBCT 3D analysis in non‐human primate model. Issue 7 (25th October 2015) - Omran, Mostafa; Min, Seiko; Abdelhamid, Alaa; Liu, Yi; Zadeh, Homayoun H.
Abstract: Aim: The aim of this study was to evaluate the efficacy of ridge preservation involving novel devices used for obturation of socket orifice (Socket cap; SocketKAP ™ ) and resorbable cage used for space maintenance in sites with facial wall dehiscence (Socket cage; SocketKAGE ™ ). Material and Methods: Eight teeth were extracted in each of six Macaca fascicularis non‐human primates. Six intervention groups consisted of the following: Group A: intact socket negative control. Group B: intact socket: socket cap. Group C: intact socket filled with anorganic bovine bone mineral (ABBM) + socket cap. Group D: dehiscence: negative control. Group E: dehiscence: socket cap + socket cage. Group F: dehiscence: filled with ABBM + socket cap + socket cage. CBCT scans were obtained preoperatively and at 6 and 12 weeks following intervention. The pre‐ and postoperative scans were superimposed, to quantify 3D volumetric alveolar bone changes. Results: Volumetric bone loss occurred in all sockets, not only within the cretal zone (0–3 mm) to the ridge crest, as has been commonly reported by other investigators, but significant bone loss was also detected in the zone which was 3–6 mm apical to the alveolar crest. For intact sockets, socket cap + ABBM led to significantly greater percentages of remaining bone volume when compared to groups A and B. A significant difference favoring socket cap + socket cage + ABBM treatment was observed for sockets with facial dehiscence defects compared to groups D and E. Conclusions: Socket cap in conjunction with ABBM appears effective in limiting post‐extraction volumetric bone loss in intact sockets, while socket cap + socket cage + ABBM appears effective in limiting post‐extraction bone loss in sockets with dehiscence defects.